2017
DOI: 10.11114/aef.v4i3.2295
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Modeling for the Spot Price of Gold Based on Influencing Factors

Abstract: In light of the special roles of the price of gold on the technological and economic development as well as social aspects of human society, it is of great importance and necessity to develop a series of statistical models that, based on sound reflection of the current structure of the gold market, are able to provide valuable references for trends of the gold price. In fact, the gold price is influenced by a variety of economic factors. For forecasting purposes, it is useful to study the shortand long-run eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Te time-series methods forecast the future gold price based on the past time series, including ARIMA (auto-regressive integrated moving average), the ARCH (auto-regressive Conditional Heteroscedasticity) class models, and the GARCH (Generalized Auto-Regressive Conditional Heteroscedasticity) class models among others. For example, Wang and Xia [6] analyzed the marginal and joint impact of economic variables on the gold price, and provided a short-term forecast of the gold price by multiple regression, achieving a satisfactory result. Yang [7] used the ARIMA model, and the results showed that the model can refect the true gold price trend to a certain extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Te time-series methods forecast the future gold price based on the past time series, including ARIMA (auto-regressive integrated moving average), the ARCH (auto-regressive Conditional Heteroscedasticity) class models, and the GARCH (Generalized Auto-Regressive Conditional Heteroscedasticity) class models among others. For example, Wang and Xia [6] analyzed the marginal and joint impact of economic variables on the gold price, and provided a short-term forecast of the gold price by multiple regression, achieving a satisfactory result. Yang [7] used the ARIMA model, and the results showed that the model can refect the true gold price trend to a certain extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gold prices are positively linked to inflation rates [1]. Thus, the major macroeconomic variables that affect the spot price of gold in the short and long terms are usually reviewed [2]. Consequently, the Federal Reserve System (FED), the West Texas Intermediate (WTI), the Inflation Expectations (INF), the Dow Jones Industrial Average (DJI), and the US Dollar Index (DXY) are all widely used to forecast the gold price [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the major macroeconomic variables that affect the spot price of gold in the short and long terms are usually reviewed [2]. Consequently, the Federal Reserve System (FED), the West Texas Intermediate (WTI), the Inflation Expectations (INF), the Dow Jones Industrial Average (DJI), and the US Dollar Index (DXY) are all widely used to forecast the gold price [1][2][3]. The FED is the central bank of the United States central bank that ensures the smooth operation of the US economy and long-term public interest rates [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the state space model, Que and Ma (2013) find that trade integration is the primary catalyst to facilitate the RMB internationalization. Some scholars (He & Chen, 2019;Wang & Xia, 2016) conclude that the rapid growth of China's economic strength and comprehensive national strength was the fundamental factor in the early development of RMB internationalization. China's economic strength is the major factor affecting the degree of RMB internationalization, followed by the degree of capital account openness.…”
Section: Introductionmentioning
confidence: 99%